Supplier segmentation: a study in an automotive industry - Rodrigo Furlan de Assis; Gabriel Henrique Rossatti Marinelli; Guilherme Giubilato Ferreira; Joni Roan Melo; Rafael Bueno Alves (GEPROS: Gestão da Produção, Operações e Sistemas, 2018)
The present study aimed to analyze a current vendor management system in a company in the automotive industry and propose a new segmentation of suppliers. Based on the survey of the theoretical framework, the work demonstrates, through a case study, how the application of ABC Curve and matrix of strategic positioning of materials can assist in the development of new strategies that optimize supply chain management with inventory cost reduction, improvement in production capacity and strengthening the relationship with suppliers. From the adoption of criteria and the analysis of the collected data, it was possible to direct, in a concrete manner, a plan of action for different types of suppliers, seeking an efficient segmentation of the supplier base. Finally, through the proposed system, it´s possible to observe how the application of supplier management tools can positively interfere directly in the growth and development of the company.